Could the issuance of CBDC reduce the likelihood of banking panic? - Soraya Ben Souissi; Mahmoud Sami Nabi (Journal of Central Banking Theory and Practice, 2023)
This paper delves into the relationship between the issu-ance of Central Bank Digital Currencies (CBDC) and the likelihoodof banking panic. The issuance of CBDC acts as a disturbing shockthat incentivizes depositors to withdraw all/part of their depositsfrom the commercial banks, to swap it for CBDC which are offeredby the central bank. We determine a variety of tools that centralbanks can use in order for the issuance of CBDC to act as a stabi-lizing factor of the banking system (by reducing the likelihood ofbanking panic).
Keywords: E31; E42; G11; 330; Central bank digital currency; liquidity; financial stability